Le nomandisme dans le roman Embroideries de Marjane Satrapi : une analyse de la théorie féminisme de Rosi Bratidotti - Amelia Atma Yunita; Novi Kurniawati (Lingua Litteria Journal, 2026)
Marjane Satrapi’s novel Embroideries depicts the lives of women within the Iranian sociocultural context, which is marked by strong patriarchal pressures, particularly regarding standards of virginity, family honor, and control over women’s bodies and sexuality. This work represents a dynamic of female identity that is not fixed but in constant transformation in its relationship with constraining social structures. This corresponds to the concept of nomadism in Rosi Braidotti’s feminism. This research aims to explain the causes of the emergence of nomadism in female identity as well as the process of its formation within the text. This research adopts a qualitative approach grounded in Rosi Braidotti’s theory of nomadic feminism. The material object of this study is the novel Embroideries, while the formal object is the nomadism of female identity analyzed through the concepts of deterritorialization and reterritorialization. Data were collected using the technique of reading and note-taking, then analyzed using content analysis, accompanied by a contextual interpretation of the text’s narratives and dialogues. The results show that the nomadism of female identity emerges due to patriarchal sociocultural pressures that limit women’s freedom in determining their life choices. The process of identity formation unfolds in two stages: deterritorialization as a form of detachment from patriarchal norms, and reterritorialization as a process of forming a new identity through reflection on women’s experiences, self-awareness, and life choices. Furthermore, the spaces for dialogue among women in the novel function as avenues for collective reflection that reinforce this process. It can be concluded that female identity in this novel is neither fixed nor essential, but is continually negotiated and transformed within patriarchal sociocultural structures. This identity shifts dynamically through the practices of deterritorialization and reterritorialization, allowing women to reconstruct their position and subjectivity